The concept of function creep. Issue 1 (2nd January 2021) - Koops, Bert-Jaap
ABSTRACT: Function creep – the expansion of a system or technology beyond its original purposes – is a well-known phenomenon. Correction: it is a well- referenced phenomenon. Yearly, hundreds of publications use the term to criticise developments in technology regulation and data governance, but surprisingly, no-one has ever written a paper about the concept itself. This paper fills that gap in the literature, by analysing and defining 'function creep'. This creates conceptual clarity that can help structure future debates and address function creep concerns. After analysing the term 'function creep' itself, I discuss concepts that share family resemblances, including other 'creep' concepts and many theoretical notions from STS, economics, sociology, public policy, law, and discourse theory. Function creep can be situated in the nexus of reverse adaptation and self-augmentation of technology, incrementalism and disruption in policy and innovation, policy spillovers, ratchet effects, transformative use, and slippery slope argumentation. Based on this, I define function creep as an imperceptibly transformative and therewith contestable change in a data-processing system's proper activity . Argumentation theory illuminates how the pejorative 'function creep' functions in debates: it makes visible that what looks like linear change is actually non-linear, and simultaneously calls for a much-needed debate about this qualitative change.